SD-IOT: Security and Privacy - Patil, Vishal S; Bhute, Suraj S; Chauhan, Gauri J; Morey, Aparna P; Borkar, Tejaswini S (International Journal of Computer Sciences and Engineering, 2019)
The Internet of things (IoT) is becoming apparent of the Internet which can connect nearly all environment devices, embedded with Internet Protocol (IP) and they are remotely monitored and controlled. Due to the huge growth of IoT devices, IoT networks are vulnerable to various security attacks. The implementation of efﬁcient privacy and security protocols in IoT networks is extremely needed to ensure authentication, conﬁdentiality, integrity and access control, among others. In this paper, I firstly present an in-depth meaning of the Internet of Things (IoT) and then propose a general framework for software-deﬁned Internet of Things (SD-IoT) based on the SDx paradigm, software-deﬁned everything (SDx) paradigm provides a way to strengthen the security of the IoT devices, as well as determines the impact of those new security and privacy issue and possible solutions. The proposed framework is implemented to strengthen the security of the IoT with heterogeneous and vulnerable devices. IoT, Software-deﬁned Internet of Things (SDIoT), Security, Privacy.